Implementasi Pola Asuh Taruna Pelayaran Berbasis Humanist Sustainable Smart Eco-Friendly Campus di Politeknik Pelayaran Sumatera Barat. - Putra, Riki Wanda; Nugraha, Markus Asta Patma; Noviandani, Nasra (Politeknik Pelayaran Sumatera Barat, 2025)
This study aims to examine the implementation of a cadet mentoring model based on a Humanist, Sustainable, Smart, and Eco-Friendly Campus at Politeknik Pelayaran Sumatera Barat (West Sumatra Maritime Polytechnic). Within the context of vocational maritime education, mentoring plays a crucial role in shaping cadets’ character, discipline, and social responsibility. A humanistic approach emphasizes respect for humanitarian values, while the principles of sustainability, smart campus design, and eco-friendliness provide a framework for developing a campus that supports holistic learning processes. The research employs a descriptive qualitative methodology using observation, in-depth interviews, and document analysis involving members of the academic community and cadets. Findings indicate that implementing a mentoring model grounded in these concepts enhances cadets’ environmental awareness, social ethics, and adaptive capacities in responding to global maritime challenges. Moreover, integrated development programs that incorporate digital technologies and environmentally friendly practices further reinforce a sustainable educational ecosystem. Recommendations include strengthening training for cadet mentors, integrating character- and environment-based content into the curriculum, and optimizing green campus infrastructure to support the realization of a smart, eco-friendly campus.